Conhecer, aprender, transformar: projeto de desenvolvimento social como espaço de práticas coletivas - Junges, Vanessa de Campos (2018)
The present dissertation aimed to understand how collective practices are configured in the Association of Recyclers of the Spring District of the Profession Project Catador. Therefore, an intersubjective and interpretative study was developed, through a qualitative and descriptive research, based on a unique intrinsic case study. The research object was the AREPRICA, which belongs to the Profession Project Catador. Data collection took place through ethnographic techniques, such as semi-structured interviews, non-participant observations and secondary data. In relation to the analysis of the data, the interpretative textual analysis was used in conjunction with the analysis of templates. The main evidence lies in the relevance of a PDS, which, when developed directly based on the needs of the community, results in positive aspects to the society as a whole, as it happened in the initiative created by UNICRUZ (developer). Still in this environment, the agents of development are pointed out, that through a long-term work, they are succeeding in reinserting the recyclers in the community, providing them with the necessary assistance, acting as mediators between developers and developed. And what is the responsibility of the developed, social and economic progress has been observed, in which they are revealed as environmental agents, and have a different life perspective. Regarding the conduction pillar of the EBC, this occurs through collective work, which dissolves in self-management and collective action. Regarding this, it was noticed that even though there are two types of recyclers in the EBC, both act based on collective work, mainly under the collective action bias, configuring a space that aims at the common good. Thus, this characteristic of the group demonstrated to facilitate the development of their collective practices in the moment of work. Under a closer look (zoom in), it was evidenced that the practices are being modeled at the moment of its realization through the actions and sayings, as well as of the interactional order. The artifacts are configured as means of support, innovation, as well as the condition so that some activities can be carried out. The practical concern stands out in the group, in which they consider the collective to act, while they can be creative, as long as its innovation does not impact negatively. Thus, the practice of recycling itself is institutionalized by its practitioners, but the activities that compose it are sometimes not recognized because they are performed in different ways. On the other hand, under a closer look (zoom out), it was verified that the texture of the EBC is composed of the individual to the institutional, that is, it connects to the individual learning, the interactions of the group, Project Profiler, buyers, events and news, as well as the laws that integrate such spaces. In this way, a network of practices is created that has several practitioners who both affect the EBC and are affected by it. Therefore, the EBC format, configured in the collective work, allows for the same growth, generating greater opportunities for work and income.